Exploring Charity Sport Events in Barcelona Province: A Phenomenon on the Rise, albeit with Pending Issues (Explorando los eventos deportivos solidarios en la provincia de Barcelona: un fenómeno en auge con asignaturas pendientes) - Sixte Abadia Naudi; Josep Cabedo Sanromà; Ricardo Sánchez Martin; F. Xavier Medina Luque; Marta Moragas Rovira; Sacra Morejon Torné (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Abstract. The purpose of this research was to analyse the main characteristics of charity runs and walks in Barcelona Province, attending at the format of the event, at the organising agents and, with a particular emphasis, at the level of accountability in the management of charitable giving at such events. Data were collected from an analysis of 189 websites for charity runs and walks. A participatory action research group contributed to the development of the analysis model, whose design guided the different stages of the research. The results show the growing popularity of events like these within the context of an ever-increasing diversity of event types and organising agents, as well as the importance placed on charitable causes. A considerable variability is observed in the criteria used for charity management, together with a very low awareness of the need to render account to stakeholders through the website of the events analysed.